Polyparasitism with malaria and intestinal parasite infections in febrile children attending General Hospital Bayara, Bauchi State, Nigeria - Muhammad, Mukhtar Adamu; Adamu, Samail Abayo; Miya, Yusuf Yahya; Muhammad, Ruqayyah Hamidu; Tanko, Ikilimatu Ibrahum; Abdulkareem, Jamil Hassan (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Background: This work was intended to detect prevalence of polyparasitism with malaria and of intestinal parasite infections in febrile children, as well as to determine the prevalence of Polyparasitism with malaria and of intestinal parasite infections in febrile children aged between 1-10 years attending General Hospital Bayara Bauchi state.Materials and methods: A cross-sectional study of febrile children admitted at General Hospital Bayara between February and October 2023 was conducted. Fresh stool and blood samples were collected, thin and thick blood film were performed using Giemsa-stained and blood film was examined for malaria parasites, while wet mount smear and zinc floatation method was done intestinal parasites infections (IPIs). The Pearson’s chi-square and multivariate analysis (MANOVA) were all carried out.Results: Six hundred and sixty-six (666) children successfully took part in this study. The overall prevalence of malaria and polyparasitism observed were 76.3%. 57.3% were found to be infected with Plasmodium falciparum specie of Malaria parasite, while polyparasites of intestinal parasites found were Ancylostoma duodenale accounting for 22.4%; 15.6% for Ascaris lumbricoides; Entamoeba histolytica 3.3%; Giardia lamblia 1.0% and Taenia specie were the least Polyparasitism accounting for 0.4%. A significant association between Malaria and Not regularly used of (LLIN) (p = 0.002) which was observed at (confidence interval of 0.01). There was no significant association in the prevalence of polyparasitism with communities of children infected with malaria (p=0.340). Conclusion: This study showed that malaria and IPIs still constitute a major public health problem in the study area despite a lack of any significant association between these infections and communities. The findings suggest that there is a need for the implementation of control measures to curb the rate of malaria and IPIs in the study area.